Theoretical and Experimental Investigations of Flat Sheet Membrane Module Types for High Capacity Gas Separation Applications. Issue 8 (17th May 2013) - Brinkmann, Torsten; Pohlmann, Jan; Withalm, Ulrike; Wind, Jan; Wolff, Thorsten
Abstract: Gas permeation is increasingly considered for high capacity applications. This contribution discusses the commonly employed membrane module types for flat sheet membranes and suggests a new module concept. The applications considered are the separation of CO2 from flue gas and hydrocarbon dewpointing of natural gas. Rigorous models for predicting the operating performance of the module types are described. Pilot plant experiments were conducted to validate the model for envelope type modules. Simulation studies were carried out to predict the performances of the different module types for the two examples and assess their advantages and disadvantages. Abstract : Gas permeation is increasingly considered for high capacity applications. Different types of flat sheet membrane modules are considered for their application in natural gas processing and for the removal of CO2 from flue gases. The operating performance of the modules is evaluated by means of experiments and process modeling.